Isolation and Identification of Pathogenic Vibrio Species in Black Rockfish Sebastes schlegeli - Xiaoling Liu; Cuirong You; Yong Zeng (Fishes, 2023)
Four pathogenic Vibrio species were isolated from three diseased black rockfish Sebastes schlegeli in Yantai, Shandong Province, China. The strains were identified based on physiological and biochemical characteristics and 16S rDNA sequencing and named SF-2, SF-3, SF-5, and SF-6, respectively. SF-2 was Vibrio scophthalmi, SF-3 was V. harveyi, SF-5 was V. alginolyticus, and SF-6 was V. parahaemolyticus. This is the first time that V. scophthalmi was isolated from black rockfish. The present research shows that V. scophthalmi is a potential pathogen. Detection of virulence genes using polymerase chain reaction showed that SF-3, SF-5, and SF-6 carried FlaB; SF-5 and SF-6 carried TcpA; and SF-2, SF-5, and SF-6 carried ToxS. Tdh, Trh, Tlh, ToxR, and Zot were not detected. SF-3, SF-5, and SF-6 all had protease, gelatinase, lipase, and lecithinase. They were all intermediately sensitive to erythromycin, whereas SF-2, SF-5, and SF-6 were sensitive to spectinomycin, and SF-3 was sensitive to cotrimoxazole and chloramphenicol. They were resistant to most antibiotics and multidrug resistance was obvious.